Sexual Health Advocacy for Guys (SHAG): a randomized trial of the impact of a text-messaging program on HIV incidence and STI testing among a national sample of sexual minority cisgender adolescent and young adult men - M. L. Ybarra; D. J. Feaster; R. Garofalo; S. Bull (Trials)
Abstract Background Disparities in sexually transmitted infections (STI) including human immunodeficiency virus (HIV) among sexual minority boys and young men are substantial. Effective HIV and STI prevention programs that include access to pre-exposure prophylaxis (PrEP) medication do not consistently include younger sexual minority men. Text-messaging programs for HIV prevention have been associated with increases in HIV testing among sexual minority adolescent boys, but these programs have not incorporated a focus on PrEP or STIs beyond HIV. Methods We will conduct a two-arm randomized trial with 1:1 allocation comparing the superiority of text messaging-based intervention focused on HIV and STI prevention to a generic HIV education program with content focused on promoting a “healthy lifestyle” (e.g., self-esteem). Outcomes include testing for HIV and other STIs, increasing PrEP and PEP use, and HIV incidence. Generalized linear models will be used to estimate treatment effects on primary study outcomes, with longitudinal models (estimated based on Generalized Estimating Equations) specified to examine effects over time. Mediation will be assessed based on a product of coefficients approach with bootstrapped standard errors. Discussion This is the first randomized controlled trial (RCT) with a national sample of cisgender sexual minority adolescent boys and young men 13-22 years of age exploring the efficacy of a text messaging-based intervention in increasing HIV and STI testing, and PReP and PEP use. Findings will inform the scalability of text messaging programs for sexual health promotion and at-home STI testing, and will demonstrate impacts of a behavioral health intervention on HIV incidence. Trial registration ClinicalTrials.gov NCT06230367 . Date of registration: 1/29/2024.